PEO‐Silsesquioxane Flexible Membranes: Organic‐Inorganic Solid Electrolytes with Controlled Homogeneity and Nanostructure. Issue 6 (24th February 2017) - Mehdi, Ahmad; Cerclier, Carole V.; Le Bideau, Jean; Guyomard, Dominique; Dalmas, Florent; Chenal, Jean‐Marc; Chazeau, Laurent; Fontaine, Olivier; Vioux, André
Abstract: Hybrid organic‐inorganic membranes with controlled nanostructures involving PEO chains and silica‐like cross‐linkers with remarkable nanoscale homogeneity were achieved by one‐pot sol‐gel process from PEO chains equipped with one or two hydrolysable silicon end‐groups. Playing on the molar ratio of mono‐ over bis‐silylated PEO precursors (up to 80%) permitted modulating the mesh size to looser networks with higher segmental motion. Typically, the influence of the nanostructure of the membranes on their electrochemical and cell performances was tested on networks filled with LiTFSI salt (with and without solvent) by means of complex impedance spectroscopy and galvanostatic cycling measurements. Abstract : Hybrid lithium ion containing membranes with a controlled nanostructure have been synthesized by sol‐gel process and investigated as advanced electrolytes by complex impedance